Language play, language learning - Cook, Guy (Guy W. D.); Oxford University Press (Oxford [England] ; New York : Oxford University Press, 2000)
"This book demonstrates the extent and importance of language play in human life, considering it at the formal level (as the patterning of sound and structure), at the semantic level (as the creation of fictions and fantasies), and at the pragmatic level ( as humour, social display, and agonistic contest). Far from being seen as a trivial or peripheral activity, language play is depicted as central to human thought, underpinning our capacity to adapt as individuals, as societies, and as a species." "The book also considers the implications of language play for language teaching. Recent theory has been preoccupied with meaning, reality, and usefulness, both as the means and the end of language learning. An understanding of language play, however, points towards a greater role in language pedagogy for attention to form, artifice, and ritual."--BOOK JACKET.
Includes bibliographical references (pages [207]-222) and index.
Keywords: Plays on words; Language and languages; Language acquisition; Play; Children -- Language